62 'Please, I want to go home' – creating a homecare team to expedite discharge home from hospital at the end of life. Issue Volume 9: Issue (2019)Supplement 1 (March 2019) - Thomson, Magdalen; McGaughey, Sarah; Platt, Tracey; Gaffney, Rachel
Abstract : Background: The project addressed delays in discharge and its impact on unnecessary acute bed occupancy, responding to 'Please, I want to go home' for dying patients. The press perceptions that the 'NHS must get a grip on hospital discharge delays', and discharge delay rise by 23% in the preceding year (NHS England) led to agreement that it was unacceptable that vulnerable and dying patients were 'stuck' in hospital. Method: A case for change put to our local CHC commissioners highlighted the lack of care capacity, CCG spot purchasing methodology, and patients with agreed fast track (FT) funding being inappropriately admitted into hospital as no care available at home. FT applications were increasing yearly, the CHC department was understaffed and challenged to meet the NHS CHC Framework timeframes, and the FT reviews were not being undertaken within 3 months. Some individuals had been on the FT pathway for 3 years. Commissioner contract aims were agreed assuring quality of service provision, a responsive service to meet individual needs, implementation within 48 hours, and over seen by the hospital palliative care team. Continuity of care, review of FT eligibility and dynamic care delivery, assured best value of NHS CHC resources whilst improved patient experience. Results: In March 2016 The Homecare service was set up within Winchester and Andover, funded by CHC fast track. The first patient was accepted on 18th July 2016. In the first 6 months the service supported 32 patients, delivered 1, 147 hours of care by Band 3 healthcare support workers 8 am to 8.30 pm, and supported by the hospital/hospice palliative care team. Fast track discharge delays were reduced from 15.3 days to less than 2 days. Conclusion: This service enabled swift patient discharge, met preference, and provided timely, high quality, flexible care. It also improved patient flow through Andover and Winchester hospitals.